AB0116 Induction of Netosis-Mediated Cell Death in Ankylosing Spondylitis Patients. (15th July 2016) - Escudero-Contreras, A.; Font, P.; Lόpez-Pedrera, C.; Ruiz-Limόn, P.; Pérez-Sanchez, C.; Barbarroja, N.; Άbalos-Aguilera, M.C.; Castro-Villegas, M.C.; Ortega-Castro, R.; Calvo, J.; Collantes-Estévez, E.; Jimenez-Gomez, Y.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease, of unknown aetiology, that mainly affects sacroiliac joints and spine, and is associated with the development of several comorbidities such as atherosclerosis. Recently, a cellular death mechanism, NETosis, has been described in neutrophils that involves the extracellular release of a meshwork of DNA nuclear and granule proteins upon activation by microorganisms and other activating molecules. Excessive generation of these meshworks, as a result of non-infectious inflammatory processes, is associated with the pathogenesis of inflammatory and autoimmune diseases, as well as with the development of atherosclerosis, thrombosis and other cardiovascular complications. Nevertheless, this process has not been described yet in AS patients. Objectives: 1) To analyze the induction of NETosis in AS patients. 2) To evaluate the relationship among NETosis markers and their correlation with disease activity, oxidative stress and endothelial function. Methods: Thirty four patients with AS and 34 healthy donors were included in the study. Disease activity was determined by BASDAI index and, CRP and ERS levels. To evaluate NETosis, purified neutrophils were stained with Sytox and visualized by fluorescence microscopy. In parallel, markers of oxidative stress, inflammation and NETosis were determined in neutrophils by flow cytometry and RT-PCR. Plasma DNA was quantified by fluorimetry. Antioxidant enzyme activities in neutrophils, as well as nitric oxide (NO) and total antioxidant capacity (TAC) of plasma were measured by specific kits. Endothelial function was determined by the post occlusive hyperaemia test using Laser-Doppler. Results: Neutrophils from AS patients displayed a significant increase in NETosis percentage compared to healthy donors that was associated with an increase in plasma DNA in these patients. In parallel, AS patients showed endothelial dysfunction, along with an increase of inflammatory markers (STAT3, TNF-α and IL-1β mRNA) in neutrophils. It was also observed an alteration of oxidative status, with an increase of catalase and glutathione peroxidase (GPx) activities, and a reduction of mitochondrial superoxide dismutase (mSOD) activity in neutrophils, as well as an increase in TAC and NO at plasma level. Correlation and association studies showed that plasma DNA levels positively correlated with CRP, oxidative damage (catalase activity and TAC) and endothelial dysfunction in AS patients. Conclusions: 1) NETosis is a cellular death mechanism occurring in AS patients. 2) NETosis induction is associated with an inflammatory and oxidative profile in neutrophils from AS patients. Thus, NETosis may act as a key mediator in disease progression and endothelial dysfunction in AS patients. Acknowledgement: Funded by JA PI-0314–2012, SER Disclosure of Interest: None declared